POLICY EVALUATION ON LOCAL ORGANIZATIONAL ARRANGEMENT OF THE REGENCY GOVERNMENT OF BANYUWANGI EAST JAVA PROVINCE: local government autonomy, restructuring of local government organizations - Astuty, Pudji (STISOSPOL WASKITA DHARMA, 2018)
The development of local governments always go hand in hand with the advancement of the Indonesian political system. This study was intended to describe in depth and systematic changes that occur, to underly reasons and implications as well as to analyze the organizational restructuring of the Local Government of Banyuwangi by using rightsizing approach. Research method type is descriptive and used qualitative research approach. The findings showed that in carrying out the organization's performance of Banyuwangi local office there are push and pull of authority between organizational units as a result of the overlapping power among institutions, and also overloaded duties and authorities due to the existing condition of slim local government organizations. The study recommended for sustainable restructuring of local government organizations in the Banyuwangi Regency.